ASOSIASI FUNGI MIKORIZA ARBUSKULA (FMA) PADA TANAMAN BINTARO (CERBERA MANGHAS LINN.) DI TANAH ALUVIAL - Yurisman, Bondan; hanuddin, Bur; dina, Wah (Universitas Tanjungpura, 2015)
Bintaro or known by botanist as Cerbera manghas is a semi mangrove plant which seed oil content could potentially be used as biofuels or renewable resources. Bintaro is known as a plant associated with mycorrhizal fungi / AMF. This research aimed to find out associated arbuscular mycorrhizal fungi with bintaro grown in unnatural conditions. Surrounding soil and root of 15 bintaro around UNTAN area were taken as samples. There were 2 types of soil, the alluvial soil (bintaro sapling and trees) and peat (bintaro seedling). There were 4373 spores from all soil samples, in alluvial soil were found 248 spores / 100 g soil, and in peat there were 378 spores / 100 g soil. Totally there were 10 genus of Glomus and 2 genus of Scutellospora found around bintaro plant in the two types of soil. The average of AMF infection was low. Key word : Bintaro, FMA, Mycorrhiza, Unnatural condition.